Neuronal Vacuolation and Spinocerebellar Degeneration in a Rottweiller Puppy - Smaniotto, Crisan; Cheng, Arthur Colombari; da Cruz, Alessandra; Ferronato, Amália; Dahm, Vinicius; Santana, Vanessa Laís Covatti de; Matos, Monica Regina de; Viott, Aline de Marco (Acta Scientiae Veterinariae, 2023)
Background: Spinocerebellar degenerations and neuronal vacuolations are alterations characterized by the formation of vacuoles in the nervous tissue, commonly called status spongiosus. This condition occurs in young Rottweiler dogs causing a disease called Neuronal Vacuolation and Spinocerebellar Degeneration. Clinically, it presents with ataxia of the pelvic limbs, which evolves to generalized ataxia, tetraparesis, and laryngeal paralysis. Histologically, spongiform and vacuolar alterations of the neuropil and neurons are highlighted. This reports a case of neuronal vacuolation and spinocerebellar degeneration in a Rottweiler puppy. Case: Necropsy was performed on the cadaver of a 5-month-old Rottweiler bitch that had been presenting with ataxia for approximately 1 month, in addition to dyspnea, pulmonary crepitations, and microphthalmia. Macroscopic evaluation revealed pale ocular and oral mucosae; marked gastric dilatation and abdominal distension; pulmonary hemorrhage and edema; hepatosplenomegaly; fatty degeneration of the liver; and congestion of meningeal blood vessels. Microscopically, histological evaluation of the spinal cord showed an increase in gray matter cellularity with marked presence of oligodendrocytes and microglia cells; moderate to severe multifocal intracytoplasmic micro- and macrovacuoles with displacement of the neurons’ nuclei to the periphery of the cell; central chromatolysis of the neurons adjacent to neurons affected by vacuolation; and mild multifocal necrosis associated with mild multifocal neuronophagia. The white matter exhibited discrete digestion chambers, in addition to marked diffuse congestion of the leptomeninges. In the cerebellum, neurons in the nerve nuclei (emboliform, globose, and fastigial) showed moderate multifocal vacuoles in the cytoplasm, whereas adjacent neurons showed central chromatolysis, necrosis, and mild neuronophagia. Additional histological findings included lymphoid hyperplasia, fatty degeneration of the liver, pulmonary edema, and pulmonary hemorrhage. Discussion: Spongiform and degenerative encephalopathies are diseases recognized worldwide, mainly in cattle and sheep. However, the identification of these changes in new species has led to the need for further investigations. In dogs, the first reports occurred in 1995 and 1997 in Rottweiler animals. This disease affects young dogs, and although its pathogenesis is not completely known, it is believed to be associated with a genetic mutation in the RAB3GAP1 gene. Clinically, it is associated with clinical neurological manifestations, including progressive ataxia of the pelvic limbs, changes in spinal reflex, disordered proprioceptive reactions, laryngeal paralysis, as well as behavioral and gait alterations. In the clinical evaluation, leukoencephalomyelopathy and neuroaxonal dystrophy should be diseases considered as possible differential diagnoses, as they present with similar alterations. However, in histological evaluation, the exclusion of both is basically due to the absence of neuronal vacuolization. Unfortunately, the definitive diagnosis is only made post mortem, through a histopathological evaluation of the nervous tissue. Because it is a disease whose pathogenesis is little known and which shows signs of having a genetic character, histopathological examination for diagnostic purposes in young animals with neurological signs is of great importance. Keywords: central nervous system, encephalopathy, histopathology, vacuolization, ataxia. Título: Vacuolização neuronal e degeneração espnocerebelar em filhote de Rottweiler. Descritores: sistema nervoso central, encefalopatia, histopatologia, vacuolização, ataxia.